PRODUCTION IMPROVEMENT STRATEGY OF COMMUNITY-BASED SALT IN PALU BAY - Rustam Abd. Rauf; Asriani Hasanuddin; Rosedi Rosedi (AGROLAND: The Agricultural Sciences Journal, 2016)
Palu is one of the main areas that have regional salinity and the management is still using the traditional way. Internal factors of inner salt farmers and external factors affecting the production of folk salt in the city of Palu. This study aims to (1) identify the internal factors that become strengths and weaknesses in increased production of community-based salt at Palu bay; (2) identify external factors that became opportunities and threats in the increased production of community-based salt in Palu Bay; (3) define an alternative strategies for improving folk’s salt production in Palu bay. SWOT analysis results indicate that the appropriate strategy in improving the community-based salt production in Palu bay is in the position of the quadrant I SO strategy (Strength-Opportunities). This strategy is implemented by the program: (1) Maximizing production by utilizing the available resources; (2) Increasing the salt farmer mastery of science that accompanied the adoption of appropriate technological innovation; and (3) Increasing capacity in marketing management and build a broader partnership. The results of the analysis obtained the best strategy QSPM the 2nd program "Improvement of salt farmer mastery of science that accompanied the adoption of technological innovations.